Ductile Streaks in Precision Grinding of Hard and Brittle Materials - Venkatesh, V. C. (Indian Academy of Sciences, 2003)

(untitled)
Ductile streaks produced during diamond grinding of hard and brittle materials have aided the subsequent process of polishing. Two novel techniques were used to study the formation of ductile mode streaks during diamond grinding (primary process) of germanium, silicon, and glass. In the first technique, aspheric surfaces were generated on Ge and Si at conventional speeds (5000 rpm). In the second technique, diamond grinding of plano surfaces on glass and Si surfaces using high speed (100,000 rpm) was carried out. Form accuracy, surface finish and ductile mode grinding streaks are discussed in this paper. It was found that resinoid diamond wheels gave more ductile streaks than metal-bonded wheels but better form accuracy was obtained with the latter. Ductile streaks were obtained more easily with pyrex rather than with BK 7 glass thus necessitating very little time for polishing. Ductile streaks appeared in abundance on germanium rather than silicon. Both the novel grinding techniques were used on CNC machining centres.